218k views
2 votes
Theo started to solve the quadratic equation (x + 2)2 – 9 = –5. He added 9 to both sides and the resulting equation was (x + 2)2 = 4. Next, he took the square root of each side. Which was the resulting equation of that step?

2 Answers

5 votes

Answer:x + 2 = ±2

Explanation:

on edge

Theo started to solve the quadratic equation (x + 2)2 – 9 = –5. He added 9 to both-example-1
User Winklerrr
by
4.6k points
0 votes

Answer:


x+2=\pm2

Explanation:

He started with
(x+2)^2-9=-5.

He add 9 to both sides and the resulting equation was


(x+2)^2=4

Next, he took the square root of each side.

The resulting equation of this step is:


(x+2)=\pm √(4)


x+2=\pm2

The required equation is:


x+2=\pm2

User Candra
by
5.0k points